Impactos do nÍvel de irrigaÇÃo e da cobertura do solo na cultura do tomateiro - Campagnol, Rafael; Abrahão, Camila [UNESP]; Mello, Simone da Costa; Oviedo, Victoria Rossmary Santacruz; Minami, Keigo (My University, 2014)
Water is an asset increasingly scarce and it has also a great influence on yield and quality of tomato crop, making its management a major factor to achieve higher profitability coupled with sustainability. The study aimed at evaluating the effects of irrigation depths (60%, 80%, 100%, 120% and 140% of ETc) and black polyethylene plastic as soil covering on yield, fruit quality and water use efficiency (WUE) in field tomato crop during the rainy season in Piracicaba, SP, Brazil. The experimental design was split plots randomly distributed into 2 x 5 factorial arrangement with four replications. No influence was observed of irrigation depths on total and marketable yield, mean weight and number of fruits per plant. The use of black polyethylene plastic as soil covering increased total and marketable yield, but decreased the content of fruit soluble solids. An increase of water use efficiency was observed by reducing water levels, and it was more pronounced when soil cover had been used.
Impacts of irrigation levels and soil cover on tomato crop
Keywords: Blossom-end rot; Mulching; Solanum lycopersicum; Water deficit; Water level